Pathway-selective Insulin Resistance and Metabolic Disease: The Importance of Nutrient Flux - Otero, Yolanda F. (American Society for Biochemistry and Molecular Biology, 2014)
Hepatic glucose and lipid metabolism are altered in metabolic disease (e.g. obesity, metabolic syndrome, and Type 2 diabetes). Insulin-dependent regulation of glucose metabolism is impaired. In contrast, lipogenesis, hypertriglyceridemia, and hepatic steatosis are increased. Because insulin promotes lipogenesis and liver fat accumulation, to explain the elevation in plasma and tissue lipids, investigators have suggested the presence of pathway-selective insulin resistance. In this model, insulin signaling to glucose metabolism is impaired, but insulin signaling to lipid metabolism is intact. We discuss the evidence for the differential regulation of hepatic lipid and glucose metabolism. We suggest that the primary phenotypic driver is altered substrate delivery to the liver, as well as the repartitioning of hepatic nutrient handling. Specific alterations in insulin signaling serve to amplify the alterations in hepatic substrate metabolism. Thus, hyperinsulinemia and its resultant increased signaling may facilitate lipogenesis, but are not the major drivers of the phenotype of pathway-selective insulin resistance.